[OP.7C.01] UROMODULIN-NACL INTERACTION ON MRNA EXPRESSION OF ION TRANSPORTERS IN ISOLATED TUBULES OF UMOD+/+ AND UMOD−/− MICE. (September 2016) - Graham, L.; Graham, D.; McBride, M.W.; Dominiczak, A.F.; Padmanabhan, S.
Abstract : Objective: UMOD−/− mice have low blood pressure and decreased salt-sensitivity indicating interactions between UMOD and sodium transport in the TAL. However, it's unclear whether the effect of UMOD is solely through interaction with cognate molecules in the TAL or whether the perturbations in physiology are more complex with involvement of both TAL and other parts of the nephron. We propose to answer this by profiling mRNA expression levels of the main ion transporters and signalling molecules in tubules from UMOD+/+ and UMOD−/− mice. Design and method: Male mice of 12 weeks of age were treated ±2% NaCl ad libitum in the drinking water for 6 weeks (n = 5 per group). Following the stimulation period mice were sacrificed, kidneys excised, and tubule isolations prepared for mRNA expression analysis utilising qRT-PCR. Results: The following transporters were differentially expressed in the UMOD−/− mice: Proximal convoluted tubule; NHE3 (down regulated during steady state and further attenuated during salt loading) and SLC26A4 (up regulated during steady state and remained unchanged during salt loading); Thick ascending limb/Distal convoluted tubule; NKCC2, ROMK, ClC-KB, Barttin, NCC, and NHE3, were all down regulated during steady state and further attenuated during salt loading, whereas SLC26A4, and Nedd4 were up regulated during steady state and remained unchanged during salt loading. TNFa was up regulated at steady state and further increased during salt loading; Macula densa; ACE2 and COX2 were up regulated during steady state and remained unchanged during salt loading, AT1 and A1AR were down regulated during steady state and remained unchanged with salt loading, and NOS1 was attenuated during steady state and remained down regulated during salt loading; finally, the Collecting ducts; SLC26A4 was up regulated during steady state and remained unchanged during salt loading and ENaC down regulated during steady state and remained unchanged with salt loading. Conclusions: This study demonstrates the impact of the absence of UMOD gene on renal transporter gene expression across the length of the nephron. Additionally, genes involved in tubuloglomerular feedback, revealing a key role of UMOD in sodium homeostasis which should lead to new therapies for hypertension by targeting this gene.